STARTEGI PT. TRI BAKTI SARIMAS (TBS) DALAM MEMASARKAN CRUDE PALM OIL (CPO) DI PASAR INDIA - Menia, Reza Herli; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Election of marketing of CPO by PT. Tri Bakti Sariman in India do not get out of strategy of PT. Tri Bakti Sariman in marketing CPO. Strategy in marketing of CPO of vital importance because company of course will experience of resistance either from internal aspect and also eksternal which one of them emulation of business which these days which progressively tighten and kompetitif. Result of research show strategy marketing of PT. Tri Bakti Sarimas relate at policy of marketing which have been conducted by policy goodness for the product of, price, distribution and promotion. In make up of quality of PT. Tri Bakti Sarimas conduct study and research analyse DOBI CPO. For the emulation of price of CPO, PT. Tri Bakti Sarimas continue to insist on and along with institute and association give input to government to revise imposition of iease weighing against all exporter of CPO and conduct hedging to product of CPO. Product increase conducted by PT. Tri Bakti Sarimas by conducting development of plantation of people through program of revitalisasi. Repair of distribution, PT. Tri Bakti Sarimas not yet feel important to conduct to repair in course of pendistrubisan. Extension of marketing, PT. Tri Bakti Sarimas target to penetrate European market.